The 4 disciplines of execution : achieving your wildly important goals - McChesney, Chris; Covey, Sean; Huling, Jim (New York : Free Press, 2012)
Do you remember the last major initiative you watched die in your organization? Did it go down with a loud crash? Or was it slowly and quietly suffocated by other competing priorities? By the time it finally disappeared, it's likely no one even noticed. What happened? The "whirlwind" of urgent activity required to keep things running day-to-day devoured all the time and energy you needed to invest in executing your Read more...
Keywords: Business planning Success in business